REINFORCING STUDENTS’ MEMORY IN LEARNING ENGLISH VOCABULARY THROUGH EDUCANDY MEDIA - Dian Ardianti; St. Asriati AM; Andi Asri Jumiaty (Indonesian Journal of Psycholinguistics, 2022)
The research aimed to find out whether the implementation of Educandy Media reinforce students memory in learning English Vocabulary of seventh grade students atwsz SMPN 3 Papalang or not. This emphasizes on reinforce students vocabulary in learning process. This research used a pre-experimental method, with One Group Pretest posttest design consisting of six meetings and treatment. The number of samples is 20 students of seventh class. The data obtained by multiple choice questions in the form of noun material around. The results of calculation using SPSS 25 showed that the everage score of students’ vocabulary development was 27,00 in pre-test, and become 75,50 in post-test. Vocabulary development is supported by the t-test value which is greater than t-table value (4,687 > 1,729). Therefore, the alternative is accepted and null hypothesis is rejected. Based on analysis of the result, the researcher concluded that using Educandy media to reinforce students’ memory and improve the vocabulary of the SMPN 3 Papalang, Mamuju is effective in teaching English vocabulary.